Association between cigarette smoking and interleukin-17A expression in nasal tissues of patients with chronic rhinosinusitis and asthma. Issue 47 (November 2016) - Huang, Chien-Chia; Wang, Chun-Hua; Fu, Chia-Hsiang; Huang, Chi-Che; Chang, Po-Hung; Chen, Yi-Wei; Wu, Chia-Chen; Wu, Pei-Wen; Lee, Ta-Jen
Abstract : Abstract: Cigarette smoke plays a substantial role in the development of airway inflammatory diseases, including asthma and chronic rhinosinusitis (CRS). Interleukin (IL)-17A might contribute to cigarette smoke-related inflammation of the airway. This study aimed to investigate the association between cigarette smoking and IL-17A expression in the nasal tissues of patients with CRS and asthma. We prospectively recruited 24 patients (13 smokers, 11 nonsmokers) with CRS and asthma and 6 patients with asthma but without CRS (control group) in a tertiary medical center. Nasal mucosa was obtained as part of the nasal surgery. Protein and mRNA levels of IL-17A in the nasal tissues were determined by immunostaining and real-time polymerase chain reaction. The number of unexpected emergency clinic visits for acute asthma attacks were higher among smokers than among nonsmokers. Interleukin-17A protein and mRNA levels in the nasal tissues of smokers were greater compared to those in the nasal tissues of nonsmokers ( P   =  0.02 both) and control patients ( P  = 0.05 and 0.04, respectively). Cigarette smoking was associated with an increase in the number of unexpected emergency clinic visits due to acute asthma attack and in the expression of IL-17A in the nasal tissues of patients with airway inflammatory diseases.